KARMA PHALA PA DA PRASTHANIKAPARWA DALAM KONTEKS PENDIDIKAN BUDI PEKERTI - HARDIYANTO, HARDIYANTO (Universitas Negeri Yogyakarta, 2003)
The Ancient Javanese Belles Letters contained lots of cultural noble values referring anti developing to the positive ones. One of the Ancient Javanese belles letters is Prasthanikaparwa. This transcript contains various social cultures like karma phala. Karma phala is associated with the good and bad behavior of mankind within which this Prasthanikaparwa transcript is reflected by the story characters, like. Dropadi. Sahadewa, Nakula, Arjuna, Bima and Yudistira. Of them, what to be worthy to follow is the behavior of Yudistira. The behaviors of them can be used as a mirror in developing the individual behavior as a manifestation of the moral education to be going to bring about a harmonious and balanced relationship to the neighbour.